Important Diseases of Buffalo in Indonesia - Tarmudji . (Indonesian Center for Animal Research and Development, 2003)
Buffalo (Bubalus bubalis) is classified as valuable asset for farmers as source of additional income, meat and draught animal power in agricultural cultivable land. For the last five years, the buffalo population in Indonesia is significantly declining from 3.0 million (1997) to 2.3 million (2001) and one of causal factors is an animal disease. Some of the important buffalo diseases in Indonesia are: Malignant Catarrhal Fever (MCF), Septicaemia Epizootica (SE), Enterotoxaemia, Surra and Fasciolosis. MCF is a fatal disease affecting buffalo. The aetiological agent is unknown and for diagnosis of MCF based on clinico-pathological finding and histopathological examination. SE is an acute infectious disease of buffalo caused by Pasteurella multocida, characterized by acute inflammation of the respiratory organ and fatal cases by acute fibrinous pneumonia. Enterotoxaemia in buffalo is caused by Clostridium perfringens type A. Cases of buffaloes death were attributable to fatal C. perfringens alpha intoxication originating from enteritis of small intestine. Surra is caused by Trypanosoma evansi. Infection in buffalo, generally shows only chronic clinical signs with loss of body weight as the major effect. Fasciolosis or Liver Fluke Disease in buffalo is caused by one or more species of Trematode (Fasciola sp.), characterized by chronic cholangitis, bile duct containing fibrosis and mineralization in the wall and Fasciola sp. in the lumen. Some factors in diseases control appear to be consisted of quick reporting, isolation and treatment for suffering animals and vaccination with a high quality vaccine for the succeptible animals. Key words: Buffalo, animal disease, disease control